The Munich Compact Light Source: initial performance measures. (22nd July 2016) - Eggl, Elena; Dierolf, Martin; Achterhold, Klaus; Jud, Christoph; Günther, Benedikt; Braig, Eva; Gleich, Bernhard; Pfeiffer, Franz
Abstract : The first commercially sold compact light source has been installed in Munich, Germany; here information on the performance of the machine, such as produced flux, source sizes and spectra, is provided. Abstract : While large‐scale synchrotron sources provide a highly brilliant monochromatic X‐ray beam, these X‐ray sources are expensive in terms of installation and maintenance, and require large amounts of space due to the size of storage rings for GeV electrons. On the other hand, laboratory X‐ray tube sources can easily be implemented in laboratories or hospitals with comparatively little cost, but their performance features a lower brilliance and a polychromatic spectrum creates problems with beam hardening artifacts for imaging experiments. Over the last decade, compact synchrotron sources based on inverse Compton scattering have evolved as one of the most promising types of laboratory‐scale X‐ray sources: they provide a performance and brilliance that lie in between those of large‐scale synchrotron sources and X‐ray tube sources, with significantly reduced financial and spatial requirements. These sources produce X‐rays through the collision of relativistic electrons with infrared laser photons. In this study, an analysis of the performance, such as X‐ray flux, source size and spectra, of the first commercially sold compact light source, the Munich Compact Light Source, is presented.